Integration Challenges and Opportunity of Implementing Non-Communicable Disease Screening Intervention with Tuberculosis Patient Care: A Mixed Implementation Study - Nunemo MH; Gidebo KD; Woticha EW; Lemu YK (Dove Medical Press, 2023)
Mengistu Handiso Nunemo,1 Kassa Daka Gidebo,2 Eskinder Wolka Woticha,2 Yohannes Kebede Lemu3 1Department of Public Health, Wachemo University, Hossana, Central Region, Ethiopia; 2Department of Public Health, Wolaita Sodo University, Wolaita, South Region, Ethiopia; 3Department of Health, Behaviour and Society, Jimma University, Jimma, Oromia Region, EthiopiaCorrespondence: Mengistu Handiso Nunemo, Department of public health, Wachemo University, Po.Box: 667, Hossana, Centeral Region, Ethiopia, Tel +251 916357401, Email menhand2011@gmail.comBackground: Despite the comorbidity, early detection and treatment of the two diseases are highly recommended; however, a few pilot studies were conducted, which are mainly focused on diabetes mellitus screening and the integration opportunity and challenges were not known. The study aimed to identify integrated implementation challenges and opportunities of non-communicable disease and risk factors screening intervention with tuberculosis patient care.Methods: A mixed implementation study design was used. Data were collected from a sample of 443 tuberculosis patients, 21 key informants and facility observations. For quantitative data, descriptive statistics for proportion were summarized in tables and figures. Four distinct implementation frame was adapted for thematic analysis of audio recordings, daily verbatim transcription, and descriptive field notes.Results: The prevalence of hypertension and diabetes mellitus among tuberculosis patients were 6.55% and 5.64%, respectively. Totally 9 subthemes and 21 new codes were developed, of which 13 and 8 new codes were developed for integrated implementation challenges and opportunities, respectively. The absence of medical equipment, skill and knowledge training, record and report system, cooperative integration, feedback, referral system, shortage of supporting agencies, and services not free were external challenges, whereas lack of trained health workers, focal persons, and increased workload and absence of awareness creation were internal challenges. Despite the challenges, the presence of health extension programs, non-governmental organizations, community health care insurance and associations for diabetes mellitus were external opportunities. Availability of assigned focal persons, trained stakeholders, guidelines, information systems and compatible tuberculosis program structure were internal opportunities.Conclusion: The majority of TB patients were not comorbid with NCDs. We build a favourable system for integrated implementation developing an integration platform and structural authority at a different organization by addressing identified challenges and applying facilitators is crucial.Plain Language Summary: Despite the comorbidity, early detection and treatment of the two diseases are highly recommended, and a few pilot studies were conducted, which are mainly focused on diabetes mellitus screening and the integration opportunity and challenges were not known.This is the first mixed implementation study of integration challenges and opportunities of implementing non-communicable diseases by the two stages of WHO stepwise screening intervention.The majority of TB patients were not comorbid with NCDs. The prevalence of hypertension and diabetes mellitus among tuberculosis patients was 6.55% and 5.64%, respectively.The absence of medical equipment, skill and knowledge training, record and report system, feedback and referral system, drugs and laboratory services are not free, lack of cooperative integration, and shortage of supporting agencies were repetitively reported challenges for integrated screening intervention.Even though the challenges, the availability of health extension programs, non-governmental organizations for TB detection at the community level, community health care insurance, associations for diabetes mellitus, assigned focal persons, trained stakeholders, guidelines, and compatible tuberculosis program structure were frequently suggested opportunities for integrated implementation of non-communicable disease screening intervention with tuberculosis care program.Therefore, to operationalize systematically integrated screening intervention, the program manager should assign a focal person, train healthcare workers and develop internal and external referral systems through communication and coordination. The policymakers should develop an integration platform and structural authority at a different organization by addressing identified challenges and applying facilitators to build a favourable system for integrated implementation of NCDs and risk factors screening intervention on TB program.Keywords: prevalence, risk factors, challenges, opportunity, non-communicable diseases